Конференція музейників в древлянській столиці - Константинов, В.О. (Питання історії науки і техніки, 2007)
В статье кратко описаны состояние и проблемы технических музеев Украины.
Эти проблемы обсуждали участники 6-ой Всеукраинской научно-практической конференции «Украинский технический музей: история, опыт, перспективы», состоявшейся в г. Коростене. In the article are briefly described a condition and problems of technical museums of
Ukraine. These problems were discussed by the participants by 6-th Ukrainian scientific -
practical conferences «The Ukrainian technical museum: a history, experience, outlook»,
holding in Korosten.